Dreaming of Change: Young Middle-Class Women and Social Transformation in Jordan - Droeber, Julia (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This anthropological monograph focuses on the everyday experiences of young, highly educated women in contemporary Jordan. It carefully analyses their powerful contributions to social change as well as the strategies they employ in dealing with the problems they generally face. In their struggle to find recognition, religion (Islam and Christianity) often plays a major part and helps them to empower themselves, which is also reflected in this account. The study discusses family relationships, social networks, gender constructions, religiousness, and women's roles in various social spheres. It sheds light on how these young women actively influence transformations in their society and re-negotiate their own and other people's social position, and how they, in turn, are highly influenced (and often restricted) by the socio-cultural environment in their efforts towards change.